2022
DOI: 10.1063/5.0088724
|View full text |Cite
|
Sign up to set email alerts
|

Gate-controlled polarization-resolving mid-infrared detection at metal–graphene junctions

Abstract: The ability to resolve the polarization of light with on-chip devices represents an urgent problem in optoelectronics. The detectors with polarization resolution demonstrated so far mostly require multiple oriented detectors or movable external polarizers. Here, we experimentally demonstrate the feasibility to resolve the polarization of mid-infrared light with a single chemical-vapor-deposited graphene-channel device with dissimilar metal contacts. This possibility stems from an unusual dependence of photores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We have shown that a versatile tool to achieve electromagnetically inequivalent contacts lies in exploiting polarization-dependent field enhancement by keen metal edges. 15,24 Such an effect may be even more pronounced for contacts with in-plane patterning, which may have either a regular (e.g., sawtooth) or fractal 33 shape. Interestingly, such detectors with one patterned contact can demonstrate nonzero photocurrent upon illumination with natural (nonpolarized) light, as we show with electromagnetic simulation in Supporting Information, Section IVb.…”
Section: Nano Lettersmentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that a versatile tool to achieve electromagnetically inequivalent contacts lies in exploiting polarization-dependent field enhancement by keen metal edges. 15,24 Such an effect may be even more pronounced for contacts with in-plane patterning, which may have either a regular (e.g., sawtooth) or fractal 33 shape. Interestingly, such detectors with one patterned contact can demonstrate nonzero photocurrent upon illumination with natural (nonpolarized) light, as we show with electromagnetic simulation in Supporting Information, Section IVb.…”
Section: Nano Lettersmentioning
confidence: 99%
“…It has been already noted that a large fraction of photocurrent in 2DM-based detectors is formed at the Schottky junction between the 2D body and metal contacts. This occurs both for visible light, where the built-in field separates electron–hole pairs, , and for long-wavelength radiation, where thermoelectric effects and current–voltage nonlinearities take place. , In a typical detector structure with 2DM placed between identical metals, the photocurrents of two Schottky junctions are exactly compensated, in agreement with symmetry requirements discussed above. Numerous works in the field dealt with contacts of dissimilar metals, ,,, which, however, requires extra technological steps and careful selection of work functions. If it was possible to “shadow” one of the Schottky junctions, the necessary asymmetry would be introduced, and one would get the desired zero-bias low-noise photodetector based on a 2D material.…”
mentioning
confidence: 99%
See 2 more Smart Citations